사이버강의 몰입, 스트레스와 문제해결에 대한 관계 - 정영선(Young Sun Chung); 김선아(Sunah Kim) (한국콘텐츠학회 논문지, 11(7), 2011)
This study aims to elucidate the relationship between the characteristics of adult learners and flow in cyber-class along with relationships among flow, stress, and problem-solving ability. The research subjects were 1044 enrolled students at Cyber University located in Seoul through voluntary on-line questionnaire. The analysis is following: The components of flow on cyber-class including enjoyment, engagement, focused attention, and time-distortion show the significant difference upon the characteristics of adult learners such as school grade, age, marital status, and number of registered classes. In addition, the flow on cyber-class has the negative relationship with stress and the positive relationship with problem-solving ability. To improve the level of flow on cyber-class, it is important to develop the new on-line class and class materials with the consideration of characteristics and diverse backgrounds of adult learners. The incorporation of various interactive evaluation can also improve the flow level of adult learners in cyber class. Finally, the learning counselling service might be essential for adult learners to experience flow on cyber-class. 본 연구는 성인학습자의 특성과 사이버강의 몰입구인간의 관련성을 살펴보고 몰입, 스트레스, 문제해결간의 관계를 밝혀 보려는데 연구목적을 두었다. 연구대상은 서울에 소재한 K사이버대학교 재학생 1044명 이였으며 학생들은 온라인설문지 형태에 자발적으로 참여하였다. 분석결과 첫째, 즐거움, 관여, 주의집중, 시간왜곡의 몰입구인에서 학년, 연령, 결혼상태, 수강신청 과목 수라는 성인학습자의 특성에 따라 차이를 보였다. 둘째, 사이버강의 몰입은 스트레스와 부적상관관계를 보였고 문제해결과는 정적상관관계를 보였다. 이 연구를 통해 성인학습자의 사이버강의 몰입향상을 구체화하는 프로그램 마련을 위해서 다음과 같은 시사점을 제시하고자 한다. 첫째, 성인학습자의 다양한 배경과 특성을 고려한 사이버강의 설계가 필요하며, 둘째, 성인학습자가 학습과정에서 몰입감을 높일 수 있도록 다양한 사이버강의 평가방법의 개발 및 적용이 필요하며, 셋째, 성인학습자들의 사이버강의 몰입향상을 제공할 수 있는 스트레스 관리와 문제해결능력을 증진시킬 수 있는 체계적인 학업상담이 필요하다.